Patient compliance following isolated mandibular fracture repair. (21st March 2017) - Radabaugh, J. Paul; Horn, Adam Van; Chan, Stephen A.; Shelton, Jared M.; Gal, Thomas J.
Abstract : Objective: Compliance with postoperative care in the maxillofacial trauma population often is considered poor. This lack of follow‐up does not seem to be a function of decreased access to care but rather its anticipated lack of utilization. The goal of this study is to identify what factors are associated with increased compliance in postoperative management of mandible fractures. Study Design: Retrospective cohort study. Methods: Using Current Procedural Terminology codes to identify maxillofacial injuries requiring operative repair, a subset of isolated mandibular fractures was identified. Age, gender, race, insurance type, travel distance, mandible fracture location, surgical approach, and complications were used as variables in univariate regression modeling to examine factors associated with compliance to postoperative care. Results: Between 2010 and 2013, 344 isolated mandible fractures were identified. A total of 83.1% of patients made their first postoperative follow‐up visit. Demographic data, fracture location, distance to medical center (odds ratio [OR] = 1, P = 0.75), type of repair, use of drains (OR = 1.27, P = 0.61), or nonabsorbable suture (OR = 1.44, P = 0.32) did not appear to be associated with compliance. No association between complications and postoperative compliance was observed (OR = 2.37, P = 0.17). Trends toward improved compliance were observed when evaluating insurance type and use of temporary fixation hardware. The presence of current tobacco use was found to be negatively associated with patient compliance (OR = 0.33, P < 0.01). Conclusion: Postoperative compliance after surgical repair is better than what is currently represented in the literature. It appears that postoperative compliance is dependent on patient‐related factors more so than what can be modified by the surgeon. Level of Evidence: 4. Laryngoscope, 127:2230–2235, 2017